BAR EBREY AND THE WORK OF IBN AL-ATHIR "AL-KAMIL FI-TTARIKH" (Conference Zone, 2022)
According to sources, Maragha at the end of the 13th century was one of the residences of the Mongolian ilkhans and was a major political and cultural center. By order of the Mongol rulers, an astronomical observatory, a hospital and a library were built here, numbering about four hundred volumes in their vaults (3). Bar Ebrey lived and worked at the observatory, created many of his works here, lectured on astronomy, history and theology